Cranioplasty Approaches for Cranial Defects: A Case Series - P. S. Manoharan; Sai Kiran Koppolu; Sonia Abraham; Jitin Mathew (Journal of the Scientific Society)
Cranial defects are commonly caused due to road traffic accidents, tumor, postneurosurgery, or congenital deformities. Protection of the cranial structures, maintaining cerebrospinal fluid dynamics, and esthetics are some of the prime considerations while restoration of such defects. The use of autograft or allograft materials such as bone from a self or another donor site from ribs, ilium, tibia, scapula, and fascia and procedures such as split-thickness cranioplasty were carried out in the past. However, in larger defects, alloplastic materials such as celluloids, methyl methacrylate, hydroxyapatite, polyethylene, silicone, and metals such as titanium, aluminum, and stainless steel, were used for restoration. Irrespective of the material of choice, it is desirable of the prosthetic material to demonstrate low thermal conductivity, optimal strength, low infection rate, longevity, close adaptation to the defect, and fixability with plates to adjacent bone. Before digital imaging, conventional impressions were made, and approximations were done to fabricate cranial plates. With the advent of digital technology and bone imaging techniques with alongside the development of printed and milled materials, accurate cranial prosthesis can be fabricated. We cannot disregard conventional techniques as these are still used in places where access to digital technology is limited and also for patients who cannot afford the cost incurred with digital technology. The case series presents one case, which was fabricated with a conventional method, and two cases with two different approaches using digital technology. The paper aims to present various advantages, limitations, and nuances needed while the fabrication of such a prosthesis with these three methods.